The Apostate Nie Yuntai’s Comparison between Christianity and Buddhism and Its Inspiration to Sino-Christian Theology thereof - SUN, Shangyang (Journal of Research for Christianity in China (JRCC), 2025)
As an important entrepreneur in the history of modern China, Nie Yuntai (1880-1953) converted to Christianity when he was 35 years old (in 1915). His conversion, which aimed primarily at national salvation as he recalled,  is an achievement of an American missionary William Wirt Lockwood（1877—1936）, not the result of reading Tolstoy’s writings as Nie himself claimed exclusively when he reconstructed his autobiography after he apostatized his belief of Jesus Christ. He made many contributions to the Church and played a rather active and important role in works of YMCA. But due to his beloved wife’s death in 1917 and his failure of business in 1924, he gradually became alienated and even hostile to Christianity. He finally defected from his belief of Christ in 1925 and converted to Buddhism, which reveals, as this article tries to argue, the characteristics of Chinese religious belief, i.e. believing only on the basis of efficaciousness. In order to justify his apostate, he published many articles and books to criticize Christianity and appraised Buddhism. His comparison between Christianity and Buddhism is not one in the sense of academic study. He defined Christianity as the religion of God, the arbitrary and belligerent religion, and Buddhism as the religion of human mind, and inclusive and peaceful religion. He tried to argue that the former is a narrow-mined, superficial, crude religion and the latter a philosophically deep and exquisite one. He looked down upon the doctrine of “justification by faith alone” as an arbitrary and self-contradictory one, which, in his eyes, neglects the meaning of good works and the subjectivity of human kind in determining human ultimate fate. On the contrary, the teaching that human being can determine his own ultimate fate, which is the production of the fusion of popular Buddhism and Confucianism, satisfies Nie very much. Although Nie’s comparison lacks the spirit of contemporary religious dialogue, it is rather instructive to the Sino-Christian theology, since it demonstrates, from a Chinese apostate’s mouth, the significance of a delicate balance between faith and works in Christian doctrine.